2018
DOI: 10.1007/s00253-018-9115-1
|View full text |Cite
|
Sign up to set email alerts
|

Inducible promoters and functional genomic approaches for the genetic engineering of filamentous fungi

Abstract: In industry, filamentous fungi have a prominent position as producers of economically relevant primary or secondary metabolites. Particularly, the advent of genetic engineering of filamentous fungi has led to a growing number of molecular tools to adopt filamentous fungi for biotechnical applications. Here, we summarize recent developments in fungal biology, where fungal host systems were genetically manipulated for optimal industrial applications. Firstly, available inducible promoter systems depending on car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 121 publications
0
37
0
1
Order By: Relevance
“…SES consists of a promoter with a core sequence and of a heterologous transcription factor which binds to repeated activating sequences placed in the promoter (Rantasalo et al 2018). Other promoters like the Aspergillus tet-on/tet-off system are useful for research purposes rather than for industrial production (Wanka et al 2016;Kluge et al 2018). As mentioned above, a source of novel promoters may be obtained investigating mRNA levels and choosing the promoter of the highest expressed genes under relevant growth conditions.…”
Section: Maximizing Transcription Of the Enzyme Gene Of Interestmentioning
confidence: 99%
“…SES consists of a promoter with a core sequence and of a heterologous transcription factor which binds to repeated activating sequences placed in the promoter (Rantasalo et al 2018). Other promoters like the Aspergillus tet-on/tet-off system are useful for research purposes rather than for industrial production (Wanka et al 2016;Kluge et al 2018). As mentioned above, a source of novel promoters may be obtained investigating mRNA levels and choosing the promoter of the highest expressed genes under relevant growth conditions.…”
Section: Maximizing Transcription Of the Enzyme Gene Of Interestmentioning
confidence: 99%
“…They used gamma rays and EMS (Ethyl Methane Sulfonate) mutagenesis to enhance the activity of phytase, for which the phytase activity was improved to 387 U/mL at 45 • C. In addition, they also reported that the mutants produced through EMS displayed greater potential of phytase production when compared to the parent strain. The developing and improving production of heterologous proteins was determined under constitutive and inducible promoters' systems (Parashar and Satyanarayana, 2016;Kluge et al, 2018). The expression of phytase genes phyA and appA2 were expressed in P. pastoris (constitutive or inducible) and Saccharomyces cerevisiae (inducible) by Lei and Kim (2005).…”
Section: Cloning and Expression Of Fungal Phytasesmentioning
confidence: 99%
“…Progeny with such negative characteristics would still be discarded, despite the amount of work already invested in them. In this context, directed genome manipulation can help to overcome the effect of deleterious point mutations (Kluge et al, 2018).…”
Section: Accepted Manuscriptmentioning
confidence: 99%